Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.4039/n06-057
|View full text |Cite
|
Sign up to set email alerts
|

Rove beetles (Coleoptera: Staphylinidae) in yellow birch-dominated stands of southeastern Quebec, Canada: Diversity, abundance, and description of a new species

Abstract: Rove beetle assemblages from forest dominated by yellow birch (Betula alleghaniensis Britt. (Betulaceae)) at two sites in southeastern Quebec were characterized in terms of composition, diversity, and relative abundance. In total, 143 species were collected over two seasons (June–August of 1999 and 2000). In the pretreatment year (1999), 88 species were found in uncut stands. In the post-treatment year, 116 species were found in treated (by patch harvesting and ground scarification) and control plots combined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 48 publications
1
38
0
1
Order By: Relevance
“…forest in QC by Klimaszewski et al (2007), an examination of RWC and CNC material revealed additional specimens from NB, as well as from across Canada and the northeastern United States.…”
Section: Resultsmentioning
confidence: 99%
“…forest in QC by Klimaszewski et al (2007), an examination of RWC and CNC material revealed additional specimens from NB, as well as from across Canada and the northeastern United States.…”
Section: Resultsmentioning
confidence: 99%
“…In the Maritime Provinces it has frequently been recorded in old-growth and mature red spruce (P. rubens) forests in decomposing mushrooms, on bracket fungi, and in compost. In Québec it was recorded in yellow birch (B. alleghaniensis) forests by Klimaszewski et al (2007b). Atheta frosti is newly recorded in British Columbia, Nova Scotia, Ontario, and Québec.…”
Section: Atheta (Microdota) Platanoffimentioning
confidence: 99%
“…NOVA SCOTIA: Cumberland Co.: Oxford, 6.VIII.1988, 7.VIII.1988, 12.VIII.1988 Philhygra clemens is newly recorded from British Columbia, Nova Scotia, and Ontario. In New Brunswick it was found in red spruce (P. rubens) forests, whereas in Québec it was found in yellow birch (B. alleghaniensis) forests (Klimaszewski et al 2007b).…”
Section: Philhygra Botanicarummentioning
confidence: 99%
See 1 more Smart Citation
“…AK, YT, BC, AB, MB, ON, QC, NB, NS (Gusarov 2002b;Klimaszewski and Winchester 2002;Klimaszewski et al 2007b;Gouix and Klimaszewski 2007;Majka and Klimaszewski 2008b;Klimaszewski et al 2008b). Th is transcontinental species was fi rst recorded from New Brunswick in Klimaszewski et al (2005) from the Acadia Research Forest (Sunbury Co.), although it was not noted as being new to the province.…”
Section: Dochmonota Rudiventris (Eppelsheimmentioning
confidence: 99%